Effectiveness Comparative of The AG-666 Condenser with Re-Design In Producing Distillate for The AT-460 Distillation Tower Feed - Kusuma, Daffa Meifan; Yuda, Dimas; Fahriani, Vera Pangni (Universitas Merdeka Malang, 2025)
PT. Sintas Kurama Perdana is the only formic acid production plant in Indonesia. The company places high attention on the daily operating conditions of its production process, ensuring that every parameter, such as flow rate, temperature, pressure, and components, is maintained according to the set point. In the production process of methyl formate and formic acid, optimization of operational conditions, especially in the heat exchanger unit, is the main focus. The shell and tube type heat exchanger, specifically with the code AG-666, is used to condense the AT-660 distillate vapor output. This study assesses whether the AG-666 is capable of total condensation without the need for the assistance of the AG-667 condenser in anticipation if the AG-667 does not function. The analysis is carried out based on the clean overall coefficient (Uc), design overall coefficient (Ud), fouling factor (Rd), efficiency, and effectiveness for actual design conditions and re-design. The data owned from the initial design of the survival is the Uc value of 1525 W/m2.K, Rd value of 0.00032 m2.K/W, efficiency of 82%, and effectiveness of 75%. The actual condition of the heat exchanger has a Uc value of 801.71 W/m2.K, Ud value of 104.62 Btu/ft.h.℉, Rd value of 0.000436 m2.K/W, efficiency of 74%, and effectiveness of 50%. Re-Design shows that increasing the number of passes (4 passes in the shell and 8 passes in the tube) allows single-stage condensation at an outlet temperature of 32 °C without non-condensable gases such as CO. Comparison between the initial design and the re-design results shows an increase in efficiency of 80% and effectiveness of 57.78%, with Uc 725.83 W/m2.K and Ud 102.27 Btu/ft.h.℉. The redesign provided better performance than the original design, although actual efficiency was slightly lower.